Effect of Adding Different Concentrations of Hydrogel on the Water Properties of Clay Soil - Talal Jaber Abd Al Khanfous, Talal Jaber Abd Al Khanfous; Qasim Badr Idress, Qasim Badr Idress; Haider Mohammed Hassan, Haider Mohammed Hassan (University of Thi-Qar Journal of agricultural research, 2024)
A field experiment was conducted in Nasiriyah, Thi Qar Governorate, Utilizing clay soil to investigate the effects of various concentrations of hydrogel (0.0, 0.05, 0.1, 0.15, and 0.2) on water properties of the soil, including moisture content , field capacity, permanent wilting point , available water, and evaporation. The experiment was carried out during the 2023 growing season, following a systematic approach to soil preparation and plot division. Hydrogel was incorporated into the soil at a depth of 10 cm, based on the dry weight of the soil. The plots were planted with Zea mays. A randomized complete block design was utilized for data analysis, with a significance level established at 0.05. The results of the experiment indicated that hydrogel significantly improved soil moisture content, field capacity, permanent wilting point, and available water, while effectively reducing evaporation from the soil surface. Notably, treatment P4 demonstrated the most pronounced enhancement in water properties, especially when compared to the control treatment (P0).These findings highlight the potential advantages of hydrogel application in enhancing soil water retention and promoting agricultural productivity , which is particularly relevant in regions experiencing water scarcity.